An absorption-free and Doppler-improved optical waveguide for diffractionless light propagation. Issue 1 (December 2017) - Cui, Ni; Gan, Ziyang; Zhang, Lida
Abstract We propose a novel scheme to realize an optical waveguide induced by an active Raman gain (ARG) process in a four-levelN -type atomic system. Because of the nature of the ARG, there are two distinct features related to the waveguide: i) It is not absorptive, on the contrary, weak gain is presented; ii) It can be improved by the Doppler effect in the sense that the dispersion is enhanced while the gain is further reduced. This is in sharp contrast to the previously considered schemes where usually the optical induced waveguide is passive and is severely attenuated by the Doppler effect. We then study the paraxial light propagation in the waveguide which shows that the propagation dynamics is lossless and diffractionless.